2015
DOI: 10.1063/1.4922380
|View full text |Cite|
|
Sign up to set email alerts
|

Fluence thresholds for grazing incidence hard x-ray mirrors

Abstract: X-ray Free Electron Lasers (XFELs) have the potential to contribute to many fields of science and to enable many new avenues of research, in large part due to their orders of magnitude higher peak brilliance than existing and future synchrotrons. To best exploit this peak brilliance, these XFEL beams need to be focused to appropriate spot sizes. However, the survivability of X-ray optical components in these intense, femtosecond radiation conditions is not guaranteed. As mirror optics are routinely used at XFE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 23 publications
2
34
0
Order By: Relevance
“…After two pulses (fluence of 0.05 J cm À2 per shot and pulse duration of 1 ns), multilayer reflectivity decreased and the period was expanded by 5% with respect to the unirradiated mirror. The interaction of X-ray FEL pulses with boron carbide was studied at LCLS (Hau-Riege et al, 2010) and SACLA (Aquila et al, 2015). The earlier of these articles described the exposure of bulk B 4 C and thin SiC films, and the latter the fluence thresholds of grazing-incidence hard X-ray mirrors coated with thin layers of ruthenium and boron carbide.…”
Section: Introductionmentioning
confidence: 99%
“…After two pulses (fluence of 0.05 J cm À2 per shot and pulse duration of 1 ns), multilayer reflectivity decreased and the period was expanded by 5% with respect to the unirradiated mirror. The interaction of X-ray FEL pulses with boron carbide was studied at LCLS (Hau-Riege et al, 2010) and SACLA (Aquila et al, 2015). The earlier of these articles described the exposure of bulk B 4 C and thin SiC films, and the latter the fluence thresholds of grazing-incidence hard X-ray mirrors coated with thin layers of ruthenium and boron carbide.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the measured damage threshold at grazing incidence is higher than that calculated under the assumption that there is no energy transport from the volume where the photons are absorbed. This is attributed to the fact that a significant amount of absorbed energy is transported away from the surface before it melts (Aquila et al, 2015;Krzywinski et al, 2015;Liu, 1982 case of the Pt coating the energy deposition range is much larger than the extinction length, the SiB 3 energy deposition length is of the same order as the extinction length. One can speculate that this could be caused by much stronger electronphonon coupling for SiB 3 originating from drastically lower atomic weight and different band structure.…”
Section: Figurementioning
confidence: 89%
“…Damage studies campaigns, related to FELs, have been performed at various sources for singleshot and normal incidence conditions [see, for example, HauRiege et al (2010), and references therein]. Recently, several damage studies at the grazing incidence condition in the hard X-ray regime were reported for single shots (Aquila et al, 2015;Koyama et al, 2013a). There have been some multi-shot studies in the ultraviolet (Hau-Riege et al, 2008) and extremeultraviolet or soft X-ray regimes (Juha et al, 2009;Sobierajski et al, 2016), which were carried out for normal incidence conditions and for non-metallic materials.…”
Section: Introductionmentioning
confidence: 99%
“…The SPB/SFX instrument is a 3 to 16 keV, forward scattering instrument [61] with a 1 µm-scale and a 100 nm-scale focus in the upstream interaction region [69,70], and optics to refocus the upstream focal point to a second interaction region further downstream (about 12 m) in the experiment hutch. This refocused beam allows for a second, in series, experiment to be performed simultaneously with a measurement in the upstream interaction region (see Figure 4).…”
Section: Spb/sfx Instrumentation and Capabilitiesmentioning
confidence: 99%